Analisis Kebutuhan Alat Muat dan Alat Angkut Pada Kegiatan Penambangan Soil di Area 242 Dengan Penerapan Metoda Antrian Untuk Memenuhi Target Produksi Clay 3000 Ton/hari - Padeni Herlita; Murad Murad (Departemen Teknik Pertambangan FT UNP, 2018)
Area 242 is a mining location located in the PT. Semen Padang area, in the process of clay mining in area 242 it uses 13 units of transport equipment and 1 piece of loading equipment. The production target for clay stripping / day is not achieved. This is due to lack of good composition of mechanical devices and the amount of waiting time that occurs on the conveyance. The purpose of this study was to calculate the productivity of the tool, calculate the harmony of the device in soil use, get the effort and reduce the queuing time on soil production in the 242 area, and get a match factor equal to 1. In this study combined between theory and field data, so that the approach to problem solving can be obtained. And the results of data processing will be analyzed to produce a recommendation. Based on the results of the study it can be concluded. First, the productivity of Kobelco SK200 on fleet 1 is 1,322.4 tons / day and the productivity of the DT Hino 500 FM260TI is 1,308.5 tons / day. Secondly, after being upgraded by 2 fleet and the addition of 1 unit of Kobelco SK200 type excavator and Kobelco SK200 productivity is 3,037.34 tons / day and DT Hino 500 FM260TI 13 units then the conveyance becomes 3006.38 tons / day. Third, efforts to reduce the queuing time to improve the composition of the tool to MF = 1. Fourth, analysis of MF calculation = 1 on fleet 1 = 13 units of Hino, fleet 2 = 13 units. Keywords: production, match factor, queuing theory, excavator, dumptruck